VD_FINDINFO Jug / 2014 / 57 vom 18. September 2013 - VD Tribunal cantonal (2013)
CONSTATATION DES FAITS, FIXATION DE LA PEINE, CONCOURS RÉEL, RESPONSABILITÉDROIT PÉNAL | 19 al. 2 CP, 47 CP, 49 al. 2 CP, 10 CPP (CH)